Innovative uses of communication technology for HIV programming for men who have sex with men and transgender persons1. Issue 2 (1st October 2014) - Allison, Susannah M; Adams, Darrin; Klindera, Kent C; Poteat, Tonia; Wolf, R Cameron
Abstract : Globally, overall rates of HIV are on the decline; however, rates among gay men and other men who have sex with men (MSM) and transgender persons are increasing. Meanwhile, there has been exponential growth in access to communication technology over the last decade. More innovative prevention and care technology‐based programmes are needed to help address the growing numbers of MSM and transgender persons living with HIV and those at risk for infection. To address this need, a meeting was hosted by the U.S. Agency for International Development (USAID) through the President's Emergency Plan for AIDS Relief (PEPFAR) and co‐sponsored by amfAR, The Foundation for AIDS Research and the National Institute of Mental Health (NIMH). The meeting brought together researchers, community implementers, advocates and federal partners to discuss the current landscape of technology‐based interventions for MSM and transgender persons and to discuss key considerations. Presentations and discussions focused on the research gaps, facilitators and barriers to programme implementation and public–private partnerships. This article summarizes the meeting proceedings and outlines key considerations for future work in this area.